Temporal flexibility options in electricity market simulation models: Deliverable D4.1 - Couto, António (2021)
ABSTRACT: This report covers the implementation of temporal flexibility options in TradeRES’ agent-based electricity market simulations models. Within this project, the term “temporal flexibility option” was defined as an asset or measure supporting the power system to balance electric demand and supply and compensate for their stochastic fluctuations stemming from, e.g., weather or consumer behaviour by adjusting demand and/or supply as a function over time or by reducing their forecast uncertainty. Other reports from the same work package of TradeRES are published almost simultaneously, each focussing on another aspect of market model enhancements. These accompanying reports address sectoral flexibility, spatial flexibility, actor types, and modelling requirements for market designs. Flexibility options covered in this report were selected with regard to a predominantly temporal characteristic, a contribution to TradeRES’ assessment of market designs, and the feasibility to be implemented in at least one of the agent based models (ABM) during the project’s lifetime. The technical aspects of “Load shedding”, “Load shifting”, “Electricity storage”, and “Real-time pricing” were selected for implementation. In addition, the following new electricity market products were selected for implementation: “Rolling market clearing”, “Trading with shorter time units”, and “Variable market closure lead times”.